Exploiting multithreaded programming on cluster architectures - Cordeiro, O.C.; Peranconi, D.S.; Real, L.C.V.; Dall'Agnol, E.C.; Cavalheiro, G.G.H. (19th International Symposium on High Performance Computing Systems and Applications (HPCS'05), 2005)
The development of programs for parallel architectures focusing to achieve high indices of performance is a hard task. The programmer must deal with two classes of problems, one related to describing the application concurrency and data dependencies, and other related to exploiting efficiently the processing resources of the architecture, in order to obtain an efficient implementation for a specific hardware configuration. Since cluster technology allows building parallel computers are highly scalable - particularly in terms of number of nodes, processors and amount of memory - programming and execution levels must be considered independently to achieve performance portability. This paper presents Anahy, an environment for exploiting high performance computing on cluster architectures. It is highlighted the Anahy programming interface and some features of its implementation as well as a performance evaluation.